O papel dos classificadores na Libras e os contextos linguísticos de suas realizações - Pinheiro, Valdenir de Souza (2022)
The complexity of Classifiers (CLs) over the sign language has challanged the linguists and the so interested scholars in the area. Just as it occurs in oral languages, research carried out on sign language characterizes the CLs as a morpheme. Due to this fact, this paper aims at comprehending how the CLs behave over the Brazilian sign language (Libras). More specifically, the main general objective of this research was to analyze the morphological composition if the CLs in Libras, having as a database the available lexicographic registers in Capovilla et al. (2017) and its linguistic contexts of occurrences. We aimed at answering the following questionings: (i) From which linguistic-theoretical perspective the Classifiers would stand?; (ii) Which role they play over on the languages that they occur?; (iii) When it comes to Libras specifically, how the classifiers act and what kind of information they add up to the occurring language? To answer those questionings, we developed qualitative research, of bibliographical review, supported by the theorical studies about the CLs, based on research about oral languages (ALLAN, 1977; GRENBERG, 1978, DIXON, 1986; AIKHENVALD, 2000) and sign languages (SUPALLA, 1980, 1982, 1986; EMMOREY, 2002; ZWITSERLOOD, 2003, 2008, 2012; FERREIRA BRITO, 1995; QUADROS; KARNOPP, 2004; BERNARDINO, 2006, 2012). The carried-out analysis has pointed out that the Libras, although lexicalized, has a much considerable group nominal CLs, to which the composition can occur in at least two ways: (i) CL grammatical morpheme incorporated with a sign; (ii) nominal verbal in which the verb requires the presence of a nominal occurrence, that is, its composition can mean a nominal CL grammatical morpheme incorporated with a verbal CL.